Change in indicators of the development of flexibility of students 13-15 years old under the influence of differentiated learning - Margarita Mameshina (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the degree of influence of differentiated learning on the level of flexibility of students in grades 7-9. Material & Methods: analysis and generalization of scientific and methodological literature, pedagogical testing, pedagogical experiment, methods of mathematical statistics. The study involved 226 children 13-15 years old. Results: in the course of the initial study, a "low" level of development of flexibility of students in grades 7-9 was revealed. In the age aspect, the wave-like nature of age-related changes was revealed, however, these differences are mostly not significant (p>0,05). In the sexual aspect, mainly significant prevalence of girls 'indicators over boys' data was revealed (p<0,01; 0,001). After the experiment, it was found that the flexibility indicators of schoolchildren of the main groups significantly improved and these differences are statistically significant (р<0,05−0,001). Conclusions: significant changes in the indicators of development of flexibility indicate the effectiveness of the introduction of differentiated motor tasks, taking into account the individual capabilities of students in grades 7-9.